1980
DOI: 10.1126/science.6246578
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Adrenocorticotropin/Endorphin-Derived Peptides: Coordinate Action on Adrenal Steroidogenesis

Abstract: A synthetic peptide, representing a portion of the 16K (16,000 dalton)-fragment sequence within the pro-adrenocorticotropin/endorphin precursor molecule, potentiates the steroidogenic action of the 1 to 24 portion of adrenocorticotropin [ACTH(1-24)] on the rat adrenal cortex. The peptide has 27 amino acid residues and consists of gamma-melanotropin with a carboxyl terminal extension. It affects both the inner and outer adrenocortical zones of hypophysectomized animals, as evidenced by a synergistic augmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…Furthermore, Page et al (32) demonstrated that the concomitant administration of a-MSH and growth hormone stimulated aldosterone secretion in hypophysectomized sodium-depleted rats, while Vinson et al (33) reported that a-MSH stimulated aldosterone production by adrenal glomerulosa cells in vitro. in hypophysectomized rats (34 tides may be involved in the regulation of aldosterone secretion. It has been shown that 13-LPH increases the level of plasma aldosterone in the rat in vivo (35).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Page et al (32) demonstrated that the concomitant administration of a-MSH and growth hormone stimulated aldosterone secretion in hypophysectomized sodium-depleted rats, while Vinson et al (33) reported that a-MSH stimulated aldosterone production by adrenal glomerulosa cells in vitro. in hypophysectomized rats (34 tides may be involved in the regulation of aldosterone secretion. It has been shown that 13-LPH increases the level of plasma aldosterone in the rat in vivo (35).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a trypsin digest of the N-terminal peptide of POMC, prepared from mouse pituitary tumor cells, and a bovine ? '3-melanotropin (MSH) synthetic peptide, representing a portion of the N-terminal peptide, have been shown to have a marked effect on the potentiation of adrenocortical response to ACTH (39,40). In another study, a naturally-occurring human pro-r-MSH glycopeptide potentiated the ACTH-induced steroidogenic response of isolated perfused rat and human adre nocortical cells (41).…”
Section: Discussionmentioning
confidence: 96%
“…The synthetic peptide y3-MSH, which represents a portion of the amino terminal or 16,000 fragment of pro-OLMC, has been shown to potentiate the stimulation of aldosterone and corticosterone production by ACTH in hypophysectomized rats (15) and isolated rat adrenocortical cells (16) but y3-MSH itself had no steroidogenic activity. In a subsequent study, ly3-MSH has been reported to stimulate aldosterone release from human adrenal adenoma cells in vitro (18).…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous injection of a synthetic peptide representing a portion of the amino terminal or 16,000 fragment of pro-OLMC, termed y3-MSH, potentiated the stimulation of corticosterone and aldosterone by (1-24) ACTH in hypophysectomized rats (15). Furthermore, the amino-terminal region of pro-OLMC has been reported to potentiate slightly but significantly the action of (1-24) ACTH in isolated rat adrenocortical cells (16).…”
mentioning
confidence: 99%